The Phonology And Morphology Of Yemeni Tihami Dialect: An Autosegmental Account - Ahmed, Abdulghani Mahdi (2010)

(untitled)
Little methodological studies are available on Arabic dialectology particularly on Yemeni Arabic dialects (YADs) (Versteegh, 1997). Linguistic and grammatical sources in Yemen are insufficient; even those being published are yet not enough to be taken as valid grammatical and linguistic references (ALHanadwah, 2005). Hence, the current study aims at exploring one of the Arabic dialects in the Yemeni context namely Yemeni Tihami dialect (YTD). Precisely, the present study is an attempt to undertake phonological investigation to achieve better understanding of these objectives: (1) to examine the nature of consonantal and vowel phonemes in YTD, (2) to investigate the distribution of phonemes in YTD, (3) to identify and describe the set of possible phonological phenomena in YTD, (4) to analyse and explain the phonological processes by using Autosegmental Theory and (5) to identify the morphological items (proclitics, enclitics, roots etc) of YTD. To accomplish the objectives of the study, the data were analysed and examined within the framework of the Autosegmental Phonology Theory and the Feature Geometry Model by Clements (1985).